1979
DOI: 10.1159/000137297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cimetidine on the Secretion of Some Pituitary Hormones

Abstract: Cimetidine infused intravenously into 6 healthy volunteers did not induce significant changes in plasma levels of prolactin (hPRL), thyreotropin (hTSH), gonadotropin (hLH and hFSH) and growth hormone (hGH). Conversely it caused a significant increase in prolactin response to TRH without modifying the hTSH response to thyreotropin-releasing hormone (TRH) and gonadotropin response to gonadotropin-releasing hormone (GnRH). Data obtained in these experiments, together with data reported in the literature, suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…By contrast, 400 mg Cim, administered iv together with TRH, more than doubled the above men¬ tioned TRH-induced Prl response. However, when other investigators stimulated the Prl release by use of a much higher TRH dose (200 pg), simultaneous iv infusion of Cim, either failed to influence the TRH-induced Prl response (Delitala et al 1979b), or augmented this response only slightly (Scarpignato et al 1979). The Prl response is clearly dose-dependent, showing a progressive increase for TRH doses ranging between 6.25 and 100 pg.…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, 400 mg Cim, administered iv together with TRH, more than doubled the above men¬ tioned TRH-induced Prl response. However, when other investigators stimulated the Prl release by use of a much higher TRH dose (200 pg), simultaneous iv infusion of Cim, either failed to influence the TRH-induced Prl response (Delitala et al 1979b), or augmented this response only slightly (Scarpignato et al 1979). The Prl response is clearly dose-dependent, showing a progressive increase for TRH doses ranging between 6.25 and 100 pg.…”
Section: Discussionmentioning
confidence: 95%
“…This response is more pro nounced in women than in men [2] and is dose-related [4]. In addition, we have shown that intravenous infusion of this drug also increases the prolac tin response to exogenous thyrotropin-releasing hormone (TRH) [17]. The site at which cimetidine stimulates prolactin release is, at present, a matter of speculation.…”
Section: Introductionmentioning
confidence: 98%
“…Cimetidine was shown to affect, in some experimental conditions, the endocrine secretions in animals and in man [19,21,23,24], However, conflicting results have been reported in the literature concerning the effect of this H2-antagonist on glucose tolerance. While a deterioration of glucose handling after long-term treatment was observed by Jefferys and Vale [16], an improvement of glucose tolerance was reported [14] after acute admin istration of this drug.…”
Section: Introductionmentioning
confidence: 99%